Effect of light therapy on delirium in older patients with Alzheimer's disease-related dementia. (May 2022) - Zou, Chenjun; Mei, Xi; Li, Xingxing; Hu, Jun; Xu, Ting; Zheng, Chengying
Abstract: Light therapy has been used as a non-pharmacologic treatment to modulate biorhythms in patients with mental and psychological conditions. These conditions include affective disorders and depression. Delirium is a syndrome characterized by an acute change in a patient's mental status. We hypothesized that light therapy might suppress delirium in patients with Alzheimer's disease (AD). A 4-week randomized controlled trial was conducted in which AD participants were randomly assigned to a treatment group or a control group. Delirium, defined by the Confusion Assessment Method (CAM), was evaluated at baseline and after 4 weeks. The Neuropsychiatric Inventory (NPI) and Zarit Caregiver Burden Interview (ZBI) were also conducted to assess the behavior of patients and the burden of their caregivers. For this study, 61 participants were initially recruited. A total of 34 and 27 participants were included in the treatment and control groups, respectively. After treatment with light therapy, the CAM score decreased during the second and fourth week. The NPI score in the therapy group also decreased during the second and fourth week. From the caregiver's perspective, after light therapy, the ZBI score significantly decreased during the second and fourth week. Compared with the control group, patients who underwent CAM and NPI assessments showed a small but significant improvement after 4 weeks of light therapy. In conclusion, a course of 4-week light therapy significantly suppressed delirium in patients with AD. The combined effects of light therapy and conventional treatment were superior to that of conventional treatment alone.